Ethics of Amnestics and Analgesics: The Role of Memory in Mediating Pain and Harm - Salis, Marina; Brenna, Connor (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
Analgesia and amnesia represent two complimentary pillars of anesthesia directed, respectively, at mitigating the experience of pain and the processes of encoding that experience into memory. These elements are typically combined in modern anesthetic techniques, but some circumstances exist – such as conscious sedation – in which the conditions of amnesia are satisfied while analgesia plays an auxiliary and often incomplete role. These activities reflect a widely held yet underrecognized belief in clinical practice that although pain experiences may be short-lived, their representation in memory and its subsequent effects on thought and emotion can have enduring consequences for patients. In this exploratory article, we delineate phenomenal and abstract ontological categories of pain experience; advance a claim that they are treated by analgesic and amnestic agents, respectively; and describe how each class of experience is uniquely able to bring about individual harm. Beginning with the question of how it can be permissible to allow any preventable experiences or memories of pain, we identify that both phenomenal and abstract pain manifest on a spectrum of severity, each with an enigmatic threshold – unique to circumstance and individual – that determines whether or not pain will translate into harm, and what permissions therefore surround its treatment. Ultimately, we find that there are compelling physiological reasons for the concurrent use of analgesics and amnestics when pain experience exceeds these thresholds, while the treatment of “sub-threshold” experience in either class is a purely ethical imperative to be balanced with considerations of the potential harms posed by the treatments themselves.